Avoidable sight loss from glaucoma: is it unavoidable?. Issue 6 (4th April 2012) - Kotecha, Aachal; Fernandes, Sofia; Bunce, Catey; Franks, Wendy A
Abstract : Aims: To review the characteristics of patients attending a tertiary ophthalmic referral centre certified as sight impaired (SI) or severely sight impaired (SSI) from glaucoma. Methods: One hundred consecutive patients certified SI/SSI from the Glaucoma Service at Moorfields Eye Hospital, London, from January 2007 were identified from the England and Wales certification of visual impairment database. Clinical and demographic data were collected from hospital case records. Results: The median (IQR) age of patients at presentation was 66.3 (55.6 to 75.3) years; median (IQR) interval to certification was 62.2 (22.5 to 129.3) months. Fifty-seven patients presented with bilateral SSI (median (IQR) age 70.4 (59.0 to 76.9) years); interval to certification was 35.4 (5.6 to 78.1) months. Seventeen patients presented with a bilateral SI (median (IQR) age 62.1 (58.7 to 68.4) years; median (IQR) interval to certification: 137.4 (64.4 to 190.4) months). Twenty-eight patients showed disease progression while under National Health Service hospital eye service care, five of whom had no certifiable visual impairment in either eye at presentation. This was attributed to inadequate intraocular pressure control; five of these patients (18%) were deemed poorly compliant to topical hypotensive medication. Conclusions: Over 80% patients on the certification of visual impairment register from Moorfields Eye Hospital with glaucoma as the primary cause had a significant visual disability at presentation, with almost two-thirds of patients presenting bilaterally 'blind'. There appear to be delays to certification. Despite being under the hospital eye service, a number of glaucoma patients still progress to certifiable visual impairment.